Gender characteristics of health-related quality of life indicators in children with high normal blood pressure and primary hypertension - Yu.V. Marushko; T.V. Hyshchak; T.V. Marushko; N.G. Kostinska; O.V. Khomych (Zaslavsky O.Yu., 2023)
Background. The study of health-related quality of life (HRQoL) has great practical importance for patients with hypertension. The aim of the work was to investigate the gender characteristics of HRQoL in children with primary hypertension and high normal blood pressure. Material and methods. One hundred and ninety-nine patients (107 boys and 92 girls) aged 9-17 years were examined. Among them, 81 children had high normal blood pressure, 44 were with stage 1 hypertension, 38 patients had hypertension stage 1 аnd 36 children had normal blood pressure. All patients underwent ambulatory blood pressure monitoring. The Ukrainian version of the PedsQL 4.0 scale was used to assess HRQoL. Results. In girls with high normal blood pressure and in the initial stages of the stable hypertension, a higher frequency of complaints of headache, dizziness, heart pain was found compared to boys, as well as a moderate and significant negative correlation between the frequency of these complaints and HRQoL indicators. The lowest PedsQL indicators were in girls with hypertension stage 2 (total score of the PedsQL 4.0 scale was 67.41 ± 9.94 points). Boys with hypertension stage 2 had normal PedsQL scores. Regardless of gender, psychosocial health indicators were found to be low in children with high normal blood pressure compared to the control group: in girls - 70.68 ± 12.46 points (р < 0.05), in boys - 70.23 ± 13.09 points (p < 0.05). The indicators of social functioning in all children did not differ from the data of the control group. Conclusions. HRQoL indicators in children aged 9-17 years with hypertension and high normal blood pressure depend on the level of blood pressure and have gender characteristics. Girls with hypertension stage 2, except for social functioning data, have worse HRQoL indicators compared to boys with stable hypertension stage 2. Children with high normal blood pressure, regardless of gender, have lower psychosocial health indicators compared to the control group. HRQoL indicators are negatively correlated with complaints of headache (more pronounced in boys), dizziness and heart pain (more pronounced in girls). These data should be taken into account when assessing the state of children with high normal blood pressure and hypertension.